2020
DOI: 10.1101/2020.12.22.423946
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying absolute gene expression profiles reveals distinct regulation of central carbon metabolism genes in yeast

Abstract: In addition to specific regulatory circuits, gene expression is also regulated by global physiological cues such as the cell growth rate and metabolic parameters. Here we examine these global control mechanisms by analyzing an orthogonal multi-omics dataset consisting of absolute-quantitative abundances of the transcriptome, proteome, and intracellular amino acids in 22 steady-state yeast cultures. Our model indicates that transcript and protein abundance are coordinately controlled by the cell growth rate via… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…In yeast, genes related to nitrogen and amino acid metabolism are among the best known to be transcriptionally co-regulated, in the nitrogen catabolite repression (NCR) and general amino acid control (GAAC) regulons (12,26). Consistently, our results show that pathways in AA metabolism are predominantly regulated by enzyme abundance (Fig 2A ) stemming from transcriptional regulation (16). A rational extension of these observations is the hypothesis that post-transcriptional control mechanisms may be similarly coordinated by pathway, which is supported by previous reports of coordinated protein translation (9) as well as transcript and protein turnover rates (46) in central metabolic pathways.…”
Section: Fig 3bsupporting
confidence: 83%
See 3 more Smart Citations
“…In yeast, genes related to nitrogen and amino acid metabolism are among the best known to be transcriptionally co-regulated, in the nitrogen catabolite repression (NCR) and general amino acid control (GAAC) regulons (12,26). Consistently, our results show that pathways in AA metabolism are predominantly regulated by enzyme abundance (Fig 2A ) stemming from transcriptional regulation (16). A rational extension of these observations is the hypothesis that post-transcriptional control mechanisms may be similarly coordinated by pathway, which is supported by previous reports of coordinated protein translation (9) as well as transcript and protein turnover rates (46) in central metabolic pathways.…”
Section: Fig 3bsupporting
confidence: 83%
“…To estimate metabolic flux, we performed flux balance analysis (FBA) (18) using the consensus yeast genome-scale metabolic model (GEM), Yeast8.4.0 (19), constraining the model using measured metabolite exchange fluxes and dilution rates (16). The feasible region of each chemostat condition was randomly sampled 1,000 times, allowing statistical significance to be calculated when fluxes were compared across conditions (20,21).…”
Section: Data Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total RP abundance were 19.5 to 23.6% (g per g total protein) in the faster-growing species (S. cerevisiae, K. marxianus, and S. stipitis),and 16.1% in the slower-growing S. pombe (SI Appendix, Fig. S11C), in line with previous studies showing that RP abundance increases linearly with specific growth rate (40,41). We then calculated the overall ribosomal translation efficiency as mg total protein per nmol ribosomes per hour and found that S. pombe has less-efficient ribosomes compared to S. stipitis, while K. marxianus and S. cerevisiae exhibited similar efficiencies (Fig.…”
Section: The Crabtree Effect Is Accompanied By Differences In Rp Content Andsupporting
confidence: 90%